The socio-economic determiners of recycling: An analysis on European countries through a macro perspective - Hüseyin Önder (Amfiteatru Economic Journal, 2018)
The growing economies and the increase in urbanization have increased the process of waste production. Recycling of the wastes resulting from economic processes through certain operations would both decrease the amount of wastes and the need for area to store them and minimize the demand for virgin resources in production. This study aims to examine the socio-economic factors that are effective on recycling from macro perspective. Therefore, a Panel Data Analysis was conducted with data of 31 European Economic Area (EEA) countries concerning the period from 2004 to 2014. In the model used in the analysis, the recycling rate is represented by the packaging waste recycling rate. As an independent variable, Education, Income, R & D expenditures, Resources and Agricultural sector added values were used. As a result of the analyses conducted in this research it was determined that education and amount of resources are in a positive relationship with recycling rate while income levels and the agriculture sector are in a negative relationship with the recycling rate.
Keywords: Q53; C33; 330; Recycling; Socio-Economic Factors; European Economic Area (EEA) countries; Panel Data